Enzymatic maceration of albedo layer from sour orange (Citrus aurantium L.) with protopectinase-se and measurement of antioxidant activity of the obtained products - Zapata Zapata, Arley David (2012)
Protopectinase-SE was used to macerate the albedo layer from sour orange (Citrus aurantium). The effect of agitation on the process was evaluated and then, antioxidant activity of the resulting preparation was determined by mean of the methodologies DPPH, ABTS, and ferric reducing antioxidant power. The following parameters were assayed: the levels of total phenols, reducing sugars, vitamin C, total flavonones, naringin, and galacturonic acid as well as the preparation’s total acidity. It was found that the use of either a reciprocal or orbital system of agitation, the latter feature achieved with flasks having internal deflectors, yielded similar maceration levels (33 g/100 g). Moreover, the antioxidant activity, as well as the concentrations of vitamin C and total flavonones was the highest with the greatest degree of tissue maceration. These results confirm the effectiveness of the method of maceration for obtaining a form of cellular disruption that result in a maximum conservation of the nutritional characteristics of the processed tissue.